Low-Temperature ORC Systems: Influence of the Approach Point and Pinch Point Temperature Differences - James Bull; Jed Pound; Jovana Radulovic; James M. Buick (Energies)
The International Energy Agency states that geothermal energy technologies could meet 15% of the global electricity demand growth, provided cost reductions continue. Organic Rankine Cycle (ORC) systems are expected to play a key role in achieving this ambitious target. Recognized for their effectiveness in converting low-to-moderate temperature heat, ORC systems are already in use in numerous installations. The performance of ORC systems is primarily influenced by operational conditions and the choice of working fluid. A key system design challenge arises from the operational conditions of ORC systems, which are closely tied to the design and sizing of heat exchange components. This study examines the effect of the pinch point temperature difference, and the approach point temperature on the thermodynamic performance of a low-temperature ORC, with cycle efficiency and the total heat transfer area of the evaporator serving as the main performance indicators. The analysis uses a parametric approach to assess ORC performance by varying pinch point and approach point temperatures for a range of suitable working fluids. An optimal design region is identified, where the trade-off between thermal efficiency and heat exchanger size is most advantageous. These results offer valuable theoretical insights for low-temperature ORC design, highlighting the importance of selecting pinch point and approach point temperatures that strike a balance between thermal and economic goals.